Analytical model for shear strength estimation of reinforced concrete beam-column joints. (15th October 2018) - Massone, Leonardo M.; Orrego, Gonzalo N.
Highlights: Panel model can represent the average response of beam-column joints. Simple material models can predict shear strength in joints. Good correlation is observed in the proposed model. Confinement effect is relevant in interior joints. Abstract: A model capable of predicting the shear response of beam-column joints subjected to seismic actions is presented. The analytical model, originally developed for walls and based on a simple physical formulation, is adapted. It considers mean stress and strain fields based on a reinforced concrete panel representing the joint, under the assumption that the principal concrete stress and principal strain directions coincide. Simple constitutive material laws are considered for concrete and steel. To estimate the shear capacity, the model satisfies the equilibrium in the longitudinal (vertical) direction. In order to analyze the accuracy of the model, a database integrated by 92 tests of exterior and interior beam-column joints is collected from the literature. Noting that the original model does not consider the effect of confinement product of adjacent elements to the connection, this effect is introduced through factors that reduce the values of the longitudinal and transverse strain used to calibrate the angle of the strut. In addition, the contribution of the transverse reinforcement in the capacity of the element is included. These modifications together with the influence of the boundary reinforcement, yields a good strength estimate for exterior and interior joints that fail in shear. When comparing with other models from the literature, it is observed that the proposed model provides one of the best correlations.